The Role Of Technology In Special Education: Enhancing Learning For Children With Disabilities - Dr. Uzma Rafique , Shazia Aslam , Arshad Ali , Tanveer Fatima , Ahsan Mukhtar (Migration Letters, 2024)
Special education has changed through technology because it now provides unique ways to reach each student and make school accessible for children with disabilities. Using assistive technologies plus information and communications tools plus adaptive learning tools helps students with different needs learn better (Drigas & Ioannidou, 2013). Special education receives technology assistance through AAC tools, speech-to-text tools, VR, and AI screening. New technologies help students learn and help teachers create better learning spaces for everyone (Woodward & Rieth, 1997). The article shows that ICT-based methods help students with autism spectrum disorders and reading difficulties achieve better learning results (Olakanmi et al., 2020). Special education technology face budget constraints as well as learning barriers for teachers and restricted access for students. The research analyzes present policy concerns and future trends to help education systems worldwide use technology to improve special education (Lewis & Rossett, 1981).